Work-Life Balance and Its Implications to the Job Satisfaction of Cikarang Family Hope Hospital Nurses - Irma Nurmaisyah; Anoesyirwan Moens; Yuli Zein (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the effect of work-life balance on job satisfaction of Cikarang family hope hospital nurses. The methods used in this study are descriptive and verifiative studies, to provide an overview of a situation. Data collection techniques using questionnaires. A sample of 45 respondents using the slovin formula. To analyze the data assisted using the SPSS program version 28. The results of this study showed that the effect of work-life balance and job satisfaction affected the performance of implementing nurses at the Cikarang family hope hospital by 49.5% and the remaining 50.5% was influenced by other variables that were not studied in this study. This shows that there are expectations of psychological involvement that can increase nurses' job satisfaction.